Μελέτη και υλοποίηση στρατηγικών τεχνητής νοημοσύνης σε περιβάλλον βιντεοπαιχνιδιών - (:unkn) unknown (My University, 2019)
Nowadays’ games become smarter and smarter with the help of the artificial intelligence. The artificial intelligence research is defined as the study of "intelligent agents": any device that perceives its environment and takes actions that maximize its chance of successfully achieving its goals. At this point, a game that is capable to understand the skill level of the user can be achieved with artificial intelligence. In the future, games will be capable to identify the skill of the user that is playing and adjust the difficulty in order to make the game more competitive and more fun to play. The main topic of our research is how to achieve the adjustment of difficulty according the user’s skill using artificial intelligence in order to nest it inside the games so as to fit the skill level of the players.
Study and implementation of technical intelligence strategies in video game environment
Keywords: τεχνητή νοημοσύνη; artifficial intelligence, unreal engine 4